ANALYSIS OF COMMUNITY LEARNING INTEREST IN ENGLISH IN FACING MEA (ASIAN ECONOMIC COMMUNITIES) IN LUBUKLINGGAU - Riance, Astri (Universitas Muhammadiyah Palembang, 2019)
The purpose of this study is to analyze people's interest in learning English in the face of MEA (ASEAN Economic Community). So that the municipal government of Lubuklinggau can take steps to improve their English-language communication skills. The goal to be achieved by this research is to obtain the results analysis of public interest in learning English, so that from the results of this analysis the government can take steps to improve Human Resources to have good communication skills to deal with the free trade era. This research was conducted through a qualitative approach with descriptive analysis methods, Tehnique of Data Collection were conducted by observasion, questionnaire, and interview. From the research conducted it can be concluded that the interestt of Lubuklinggau community in learning English must still be increased in order to progress the Lubuklinggau region tobe advance.